A fiumei kikötő változó szerepe a magyar viszonyrendszerben, különös tekintettel a Trianon utáni agrárexportra - Bali, Lóránt (Közép-Európai Közlemények, 2014)
After the First World War as a result of the Treaty of Trianon, Hungary lost Fiume which was the only sea exit of the Hungarian economy. The Hungarian foreign trade policy and did everything in order to re- establish the city for the use of a sea exit and also tried alternative access options to the sea. Hamburg , Stettin, Trieste and Braila between were included in the alternatives. The role of the latter was more and more appreciated as a result of the start of the Danube river - sea shipping. The Hungarian agricultural export and import used primarily these ports. The importance and share of each port was highly crop yield specific. In any case it should be noted that during the period between the two world wars, the Hungarian maritime commerce did not regain the old splendor. Fiume suffered a significant prestige decline.